Relationship between sleep duration and hearing loss among adults aged 20–69: exploration of the U–shaped curve pattern - Yang, Xiaorong; Ju, Keke; Wu, Ruikai; Liu, Boxin; Zhao, Qingxia; Jiang, Tingting (Frontiers in Neuroscience, 2025)
ObjectiveThe National Health and Nutrition Examination Survey (NHANES) data were used to explore the relationship between sleep duration and hearing level among adults aged 20 to 69 years, aiming to verify the association between abnormal sleep duration and hearing loss (HL).Study designCross-sectional prevalence study.SettingThe study utilized data from the NHANES, a large-scale, population-based, cross-sectional survey conducted in the United States. The NHANES is carried out by the National Center for Health Statistics (NCHS) to assess the health and nutritional status of the civilian, non-institutionalized US population.MethodsThis study was based on the NHANES data from 2015 to 2016 and 2017 to 2020. A complex multistage probability sampling method was used to select adults aged 20–69 years. After excluding individuals with missing data, 4,883 participants were finally included. Sleep duration was collected through questionnaires, and hearing measurements were conducted by professional staff in mobile examination centers, including PTA at low frequencies, speech frequencies, and high frequencies. Statistical analysis was performed using a weighted linear regression model, adjusting for confounding factors such as gender and age. The restricted cubic spline (RCS) method was used to explore the non-linear relationship between sleep duration and hearing threshold. All statistical analyses were completed in the R environment, and p-value < 0.05 was considered statistically significant.ResultsThere was a U–shaped curve relationship between sleep duration and hearing threshold (p-overall trend < 0.001, p-non-linearity < 0.001), with the critical turning point at 8 h of sleep. Before this turning point, increasing sleep duration had a protective effect on the hearing threshold; after the turning point, excessive sleep duration led to an increase in the hearing threshold. After stratification by gender and age, a U–shaped curve relationship between sleep duration and hearing threshold was still observed in men and the elderly (p-overall trend < 0.001, p-non-linearity < 0.001). However, no dose–response relationship between sleep duration and hearing threshold was observed in women, young adults, and middle-aged adults (p-overall trend = 0.295, p-non-linearity = 0.158; p-overall trend = 0.447, p-non-linearity = 0.315; p-overall trend = 0.156, p-non-linearity = 0.777).ConclusionThere is a U–shaped curve relationship between sleep duration and hearing threshold, with the turning point at 8 h. Both short and long sleep durations have an adverse effect on hearing, and this phenomenon is particularly significant in men and the elderly. Future research needs to increase the sample size and adopt a prospective longitudinal study design. Meanwhile, Mendelian randomization and basic experimental studies can help to explore the underlying mechanisms in depth. Developing corresponding preventive strategies may help to reduce the potential burden of HL.